THE ASSOCIATION BETWEEN THE PREMENSTRUAL SYNDROME WITH VITAMIN D AND CALCIUM STATUS AMONG UNIVERSITY STUDENTS - Mahmood, Maryam Bakr; Shamdeen, Mayda Y.; Abdulrahman, Tavge Rawf (Journal of Sulaimani Medical College, 2019)
Background Premenstrual syndrome causes both psychological and physiological adverse effects on women in reproductive age. Calcium and vitamin D may have an effect on the development of premenstrual syndrome through their relationship to endogenous estrogen. Objectives The current study aimed to assess student’s calcium serum level and vitamin D level and determine their relation with premenstrual syndrome among Sulaimani University students. Material and Method This observational study included 42 female students (21 participants diagnosed with Premenstrual syndrome and 21 participants as their controls) within the age ranges from 21-29 years who were students in Sulaimani University from March 2018 to March 2019. Serum level of Calcium and vitamin D were measured for each of them. Data collected by questionnaire form and data analysed by SPSS and for the relationship between variables Chi-square and T-test used. Results Students in both of control and premenstrual syndrome cases had a deficient level of vitamin D, with the level of 15.51±8.64 ng/ml and 13.09±6.02 ng/ml subsequently with non-significant relation. The level of serum calcium was below normal range in the premenstrual syndrome group (8.21±3.3 mg/dl) compare with the control group (9.01±0.47 mg/dl) was in normal range with significant relationship between case and control group (P-value 0.03). Conclusion The mean level of vitamin D was below the normal range in both case and control groups but they were lower in Premenstrual Syndrome cases compared with control cases among students in Sulaimani University and the mean level of serum calcium was low in case group with significant relation between case and control groups. Keywords: Premenstrual Syndrome, Vitamin D, Serum Calcium.
Keywords: Premenstrual Syndrome; Vitamin D; Serum Calcium